The Purification effect on Organoleptic Profile, Yield, Total Phenol and Total Flavonoids from 96% Ethanol Extract of Moringa (Moringa oleifera. L) leaves. - Bayu Herdi Al Huda; Hari Susanti; Nining Sugihartini (Fakultas Farmasi Universitas Setia Budi, 2020)
Purification extract ethanol 96% of Moringa dry leaves was carried out to increase the active substance content and to obtain a more attractive color. The purpose of this study was to determine the type of solvent in the fractionation which provides a higher active substance content than the extract. This research begins with maceration of dried Moringa leaves with 96% ethanol. The filtrate that has been dried then purified. Purification begins with dissolving the extract in hot distilled water with a ratio of 1:10, after that ethyl acetate or n-hexane is added to the same amount as hot distilled water in a separating funnel, shaking it. The ethyl acetate or n-hexane phase is taken then the filtrate obtained is combined. The 96% ethanol extract (E1), ethyl acetate (E2) and n-hexane (E3) were then evaluated with parameters of organoleptic, % yield, total phenol, and total flavonoids. Data were analyzed statistically one way ANOVA with confidence level of 95%. The measurement results for E1, E2, and E3 in the yield were 15.81%;22.18%;20%, the total phenol was 28.94±0.54mgGAE/g; 29.44±0.93mgGAE/g; 11,41±0,12mgGAE/g, and total flavonoids 3,19±0.13%; 9,92±0.06%; 5.81±0.18% respectively. The consistency, smell and taste, all are identical, while in color, E2 is more yellowish green and brighter, making it more attractive. Statistically, there were significant differences between E1, E2, and E3 in total phenols and flavonoids. Thus it can be concluded that E2 significantly higher total phenol and flavonoids than E1 and E3.